ATLAS-T questionnaire for the detection of reading and writing problems in work contexts - Sánchez, Auxiliadora; López Méndez, Francisco; Flores, Amanda; López-Zamora, Miguel (Revista de Investigación en Logopedia, 2024)
Abstract Developmental dyslexia affects not only reading skill, but also areas such as writing, memory and executive functions. These difficulties extend beyond school into working and personal life. Starting a job and subsequent performance in relevant tasks such as organisation, note-taking and memorisation can be a real challenge for dyslexics. However, despite the personal, economic and work-related repercussions, there are hardly any tools in Spanish that investigate the literacy problems that people with developmental dyslexia experience in their working life. This study aims to validate a questionnaire, the ATLAS-T, for Spanish-speaking adults of working age with a diagnosis of dyslexia. After administering it to 87 adults with dyslexia and 175 adults without dyslexia in a control group, three types of analysis were carried out. Firstly a discriminant analysis to study the responses to the questionnaire, secondly a binomial linear regression analysis to study the predictive capacity of the questionnaire for literacy problems that would predict the presence of dyslexia, and thirdly a linear regression analysis with two demographic variables to study whether this group was more likely to attend basic education and perform jobs with a lower literacy profile. The results confirmed the methodological consistency of the self-report, its ability to detect literacy problems and the replication of the results obtained in English. Differences with Anglo-Saxon studies are also reported, such as that people with dyslexia in Spain do not have a higher job turnover or lower job satisfaction than normal readers. The paper concludes that the ATLAS-T questionnaire is a valid tool for the detection and study of literacy problems in the work environment, which can help people with dyslexia.